Additively Manufactured Micro‐ and Nano‐ Al/PVDF Ignition Sensitivity and Burning Characterization. Issue 4 (31st January 2023) - Uhlenhake, Kyle E.; Collard, Diane N.; Hoganson, Alexander C.; Brown, Alex D.; Fox, Sara; Örnek, Metin; Rhoads, Jeffrey F.; Son, Steven F.
Abstract: Aluminum (Al) and polyvinylidene fluoride (PVDF) composites can be used in many unique applications in the field of energetic materials. Due to their low melting point, many PVDF composites can be additively manufactured. However, more research is needed to better understand the ignition and combustion of these materials. Manipulating the size of aluminum (Al) particles in Al/PVDF composites can drastically alter the burning rate, ignition characteristics, and possibly flame temperatures. This study characterizes the ignition of additively manufactured micro‐ and nano‐ Al/PVDF composites through hotwire ignition tests. Both nAl and μAl particles were mixed in PVDF at 20 wt.% and additively manufactured into disks via fused filament fabrication. The nAl/PVDF printed disks ignited at a minimum ignition power (MIP) of 4.1 W compared to the 9.5 W required for ignition of μAl/PVDF disks. At identical powers, ignition delays were significantly shorter for nAl/PVDF disks. Additionally, while the nAl/PVDF disks reacted instantaneously at any power above their MIP, the μAl/PVDF disks exhibited smaller, localized flames before complete combustion, if the power was below 17.5 W. Flame temperatures were estimated through three‐color pyrometry and compared to thermochemical equilibrium calculations. While theoretical flame temperatures for nAl/PVDF and μAl/PVDF are 2023 K and 2314 K respectively, both samples burned near 2000 K when measured using pyrometry. Abstract :